A new array concept using spatially distributed subarrays for unambiguous GNSS interference mitigation in automotive applications. Issue 1 (20th March 2020) - Brachvogel, Marius; Niestroj, Michael; Zorn, Soeren; Meurer, Michael; Hasnain, Syed N.; Stephan, Ralf; Hein, Matthias A.
Abstract: Radio frequency interference (RFI) poses a severe problem for conventional GNSS receivers. Even low powered RFI can block the reception of satellite signals and prevent a position determination. Antenna array systems have been proven suitable to counteract RFI by incorporating spatial processing techniques. The large size of uniform rectangular arrays (URA) with half‐wave antenna spacing impedes an installation in cars intended for the consumer mass market, where a hidden installation is a strict requirement by industry and customers. This paper introduces a new approach, where a conventional URA is split into distributed linear subarrays with the aim to reduce their footprint but to maintain the possibility of spatial processing. The achievable gain in robustness against RFI is evaluated. Drawbacks in terms of manifold ambiguities and their consequences for spatial processing techniques are also discussed. Furthermore, the accuracy of positioning results derived from a field test is put into context with a single antenna receiver.